2003
DOI: 10.1073/pnas.0337527100
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of cortical representation through backward conditioning

Abstract: Temporal stimulus reinforcement sequences have been shown to determine the directions of synaptic plasticity and behavioral learning. Here, we examined whether they also control the direction of cortical reorganization. Pairing ventral tegmental area stimulation with a sound in a backward conditioning paradigm specifically reduced representations of the paired sound in the primary auditory cortex (AI). This temporal sequence-dependent bidirectional cortical plasticity modulated by dopamine release hypothetical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…However, these studies once again demonstrate that the adult auditory cortex remains plastic for attended, rewarded stimuli. It has been suggested that the interaction of auditory inputs, neuromodulator release, and top-down influences from higher auditory areas contribute to this learningbased cortical plasticity (20,(47)(48)(49)(50)(51)(52)(53)(54)(55). The fact that passive exposure to the same stimuli, when not reliably coupled to reward, has no measurable effect on frequency selectivity and tonotopicity of A1 in the present study again supports the conclusion that top-down modulation contributes significantly to learning-induced cortical plasticity in the adult brain (20).…”
Section: Discussionsupporting
confidence: 77%
“…However, these studies once again demonstrate that the adult auditory cortex remains plastic for attended, rewarded stimuli. It has been suggested that the interaction of auditory inputs, neuromodulator release, and top-down influences from higher auditory areas contribute to this learningbased cortical plasticity (20,(47)(48)(49)(50)(51)(52)(53)(54)(55). The fact that passive exposure to the same stimuli, when not reliably coupled to reward, has no measurable effect on frequency selectivity and tonotopicity of A1 in the present study again supports the conclusion that top-down modulation contributes significantly to learning-induced cortical plasticity in the adult brain (20).…”
Section: Discussionsupporting
confidence: 77%
“…Thus, our results indicate that the motor cortex can be a causal origin of the RTBM without signals from the prefrontal and parietal cortices, which are presumably required for cognitive strategies 5,10 . In the auditory cortex, forward conditioning of pure tone stimulation and electrical stimulation of dopaminergic ventral tegmental neurons increased the size of the cortical area responding to the tone frequency, and backward conditioning reduced the size of the area 30,31 . This bidirectional remodeling may share the same underlying mechanisms as RTBM in the motor cortex, although RTBM in the motor cortex was faster.…”
Section: Discussionmentioning
confidence: 99%
“…Dopaminergic fibers have been found in the AC (Campbell et al 1987;Harper and Wallace 1995;Goldsmith and Joyce 1996). Neuronal plasticity in the AC is evoked by paired auditory and electrical stimulation of the ventral tegmental area (Bao et al 2001(Bao et al , 2003. Effects of D2 family antagonist on sound sequence discrimination learning.…”
Section: Dopaminergic Inputs To the Ac Required For Sound Sequence DImentioning
confidence: 99%
“…Dopamine facilitates the induction of long-term potentiation (LTP) and long-term depression (LTD) in the neocortex (Law-Tho et al 1995;Otani et al 1998;Blond et al 2002). Neuronal plasticity in the AC is induced by sound stimulus paired with electrical stimulation in the ventral tegmental area (Bao et al 2001(Bao et al , 2003. In our previous behavioral study, water-deprived rats were trained to discriminate between sound sequences using a reward of water (Kudoh et al 2004).…”
mentioning
confidence: 99%